Isomorphism classes and invariants of finite dimensional filiform Leibniz algebras - Rakhimov, I. S.; Atan, K. A. M. (2011)
This talk concerns the classification problem of finite dimensional filiform Leibniz algebras. We suggest an invariant approach to the problem. It is well known that the class of complex filiform Leibniz algebras consists of three subclasses. One of these classes contains the class of filiform Lie algebras. For each class we give isomorphism criteria and find orbit functions. Then we apply this approach to classify the algebras in low dimensions cases. Classifying the filiform Leibniz algebras we inspect and reconcile the classification lists of filiform Lie algebras given before by Gomez, J.R., Jimenez-Merchan, A., Khakimdjanov, Y. in Journal of Pure and Applied Algebra, 130, (1998), 133–158.